Resting-State Striato-Frontal Functional Connectivity is Sensitive to DAT1 Genotype and Predicts Executive Function - Gordon, Evan M.; Devaney, Joseph M.; Bean, Stephanie; Vaidya, Chandan J. (Cerebral cortex (New York, N.Y. 1991), 2015)
Individual differences in striatal dopamine (DA) signaling have been associated both with individual differences in executive function in healthy individuals and with risk for psychiatric disorders defined by executive dysfunction. We used resting-state functional connectivity in 50 healthy adults to examine whether a polymorphism of the dopamine transporter gene (DAT1), which regulates striatal DA function, affects striatal functional connectivity in healthy adults, and whether that connectivity predicts executive function. We found that 9/10 heterozygotes, who are believed to have higher striatal DA signaling, demonstrated stronger connectivity between dorsal caudate (DC) and insular, dorsal anterior cingulate, and dorsolateral prefrontal regions, as well as between ventral striatum and ventrolateral prefrontal cortex, than 10/10 homozygotes. Across subjects, stronger DC-seeded connectivity predicted superior N-back working memory performance, while stronger ventral striatum-seeded connectivity predicted reduced impulsivity in everyday life. Further, mediation analysis suggested that connectivity strength mediated relationships between DAT1 genotype and behavior. These findings suggest that resting-state striato-frontal connectivity may be an endophenotype for executive function in healthy individuals.